(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate the efficacy and safety of topical Insulin in patients with persistent epithelial corneal defects. Subjects and methods: 11 eyes in 10 patients with refractory persistent epithelial corneal defects were treated with topical Insulin (1 IU actrapid per 1 ml of 0.4% Polyethylene glycol 400 solution), applied 4 times daily in addition to standard supportive care. Topical Insulin was administered as an off-label ophthalmic therapy, with written informed consent obtained from all patients prior to treatment. Follow-ups were performed at 1 week, 2 weeks, 3 weeks, 4 weeks, 8 weeks and 12 weeks. Changes in epithelial defect size, wound healing rate, symptom improvement, and adverse effects were documented. Slit-lamp corneal photos were analyzed using the ImageJ software. Results: The causes of persistent epithelial corneal defects were attributed to neurotrophic keratitis resulting from limbal stem cell deficiency, herpetic ulcer complication, infectious keratitis, chemical burn, ocular cicatricial pemphigoid and Stevens-Johnson syndrome. The median age was 55 years (interquartile range [IQR], 46-69 years). The median initial epithelial defect area was 6.48 mm² (IQR, 1.89-13.49 mm²). Ten of 11 eyes achieved complete epithelial healing within a median time of 35 days (IQR, 21-49 days). No adverse effects were observed. Conclusion: Our case series suggests that topical Insulin may be an effective adjunctive therapy for persistent epithelial corneal defects, even in patients with a history of corneal transplantation or severe ocular surface diseases.